Advances in research on small colony variants of Staphylococcus aureus - Zhiyi Ye; Tianchi Chen; Qi Zhang; Weiyi Huang; Lei He (The Microbe, 2025)
Small colony variants (SCVs) of Staphylococcus aureus have emerged as critical contributors to persistent and recurrent infections, posing significant challenges in clinical management. Characterized by slow growth, reduced metabolic activity, and increased antibiotic resistance, SCVs adapt to hostile environments through metabolic and regulatory changes. This review synthesizes current advancements in understanding the formation, clinical significance, detection, and treatment of S. aureus SCVs, with a specific focus on summarizing the mechanisms underlying clinically prevalent unstable SCVs and experimentally characterized stable SCVs. We emphasize the role of metabolic deficiencies, such as in heme and menaquinone biosynthesis, in SCV formation and persistence. Regulatory systems, including Agr, SigB, and SarA, are highlighted for their involvement in biofilm formation and immune evasion. Advances in molecular diagnostic tools and emerging therapeutic strategies, such as combination antibiotic regimens and novel inhibitors, are discussed. Understanding SCVs’ unique adaptations is crucial for developing targeted interventions to combat chronic S. aureus infections.